Diagnosis and treatment planning in dentistry - edit by Stephen J. Stefanac; Samuel P. Nesbit (Elsevier, 2017)
Develop your skills in evaluation and dental treatment planning for all types of patients! Diagnosis and Treatment Planning in Dentistry, 3rd Edition provides a full-color guide to creating treatment plans based on a comprehensive patient assessment. Using evidence-based research, this book shows how risk assessment, prognosis, and expected treatment outcomes factor into the planning process. New chapters cover patient diagnosis and team-based treatment planning, and a new Evolve website includes videos and decision-making algorithms. Written by experienced dentistry educators Stephen Stefanac and Samuel Nesbit, this book is the only dental resource that combines patient examination and oral diagnosis with treatment planning.